Unintended consequences of economic sanctions for human rights: Conflict minerals and infant mortality in the Democratic Republic of the Congo - Dominic P. Parker; Jeremy D. Foltz; David Elsea (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Are victims of human rights abuses better off with or without economic sanctions targeted at their perpetrators? We study this question in the context of a US human rights policy, Section 1502 of the 2010 Dodd-Frank Act. By discouraging companies from sourcing 'conflict minerals' from the eastern Democratic Republic of the Congo, the policy has acted as a de facto boycott on mineral purchases that may finance warlords and armed militias. We estimate the policy's impact on mortality outcomes of children born prior to 2013 and find that it increased the probability of infant deaths in villages near the regulated 'conflict mineral' deposits by at least 143 per cent. We find suggestive evidence that the legislation-induced boycott did so by stunting mother consumption of infant health care goods and services.
Keywords: F51; I15; O17; Q34; 330; sanctions; infant mortality; conflict minerals; Dodd-Frank Act; Democratic Republic of the Congo; resource certification